Characterising Distinct Migratory Profiles of Infiltrating T-Cell Subsets in Human Glioblastoma - Kollis, Paris M.; Ebert, Lisa M.; Toubia, John; Bastow, Cameron R.; Ormsby, Rebecca J.; Poonnoose, Santosh I.; Lenin, Sakthi; Tea, Melinda N.; Pitson, Stuart M.; Gomez, Guillermo A.; Brown, Michael P.; Gargett, Tessa (Frontiers in Immunology, 2022)
Glioblastoma is the most common and aggressive form of primary brain cancer, with no improvements in the 5-year survival rate of 4.6% over the past three decades. T-cell-based immunotherapies such as immune-checkpoint inhibitors and chimeric antigen receptor T-cell therapy have prolonged the survival of patients with other cancers and have undergone early-phase clinical evaluation in glioblastoma patients. However, a major challenge for T-cell-based immunotherapy of glioblastoma and other solid cancers is T-cell infiltration into tumours. This process is mediated by chemokine-chemokine receptor and integrin-adhesion molecule interactions, yet the specific nature of the molecules that may facilitate T-cell homing into glioblastoma are unknown. Here, we have characterised chemokine receptor and integrin expression profiles of endogenous glioblastoma-infiltrating T cells, and the chemokine expression profile of glioblastoma-associated cells, by single-cell RNA-sequencing. Subsequently, chemokine receptors and integrins were validated at the protein level to reveal enrichment of receptors CCR2, CCR5, CXCR3, CXCR4, CXCR6, CD49a, and CD49d in glioblastoma-infiltrating T-cell populations relative to T cells in matched patient peripheral blood. Complementary chemokine ligand expression was then validated in glioblastoma biopsies and glioblastoma-derived primary cell cultures. Together, enriched expression of homing receptor-ligand pairs identified in this study implicate a potential role in mediating T-cell infiltration into glioblastoma. Importantly, our data characterising the migratory receptors on endogenous tumour-infiltrating T cells could be exploited to enhance the tumour-homing properties of future T-cell immunotherapies for glioblastoma.